THE METHOD OF DETERMINING THE POSITION OF THE ANCHOR ON THE VALUE OF THE INDUCTANCE OF THE WINDING OF THE RELAY - Gavryliuk, V. I.; Profatylov, V. I. (Science and Transport Progress, 2007)
The method of definition of a relay anchor situation on inductance of a winding of the relay is offered in the given paper. The method is based, that the working air backlash decrees at the switching on a relay. It follows to the increase of winding inductance, which does not depend on a current practically and it determined by size of an air backlash between an anchor and core. It allows us to automation measurements of mechanical parameters of electromagnetic relays of railway automatics without removal of casing in the accordance with the operating-technical requirements.